Complete Genome and Clinicopathological Characterization of a Virulent Newcastle Disease Virus Isolate from South America - Diel, Diego G. (American Society for Microbiology, 2012)
Newcastle disease (ND) is one of the most important diseases of poultry, negatively affecting poultry production worldwide. The disease is caused by Newcastle disease virus (NDV) or avian paramyxovirus type 1 (APMV-1), a negative-sense single-stranded RNA virus of the genus Avulavirus, family Paramyxoviridae. Although all NDV isolates characterized to date belong to a single serotype of APMV-1, significant genetic diversity has been described between different NDV isolates. Here we present the complete genome sequence and the clinicopathological characterization of a virulent Newcastle disease virus isolate (NDV-Peru/08) obtained from poultry during an outbreak of ND in Peru in 2008. Phylogenetic reconstruction and analysis of the evolutionary distances between NDV-Peru/08 and other isolates representing established NDV genotypes revealed the existence of large genomic and amino differences that clearly distinguish this isolate from viruses of typical NDV genotypes. Although NDV-Peru/08 is a genetically distinct virus, pathogenesis studies conducted with chickens revealed that NDV-Peru/08 infection results in clinical signs characteristic of velogenic viscerotropic NDV strains. Additionally, vaccination studies have shown that an inactivated NDV-LaSota/46 vaccine conferred full protection from NDV-Peru/08-induced clinical disease and mortality. This represents the first complete characterization of a virulent NDV isolate from South America.